2001
DOI: 10.1139/bcb-79-3-289
|View full text |Cite
|
Sign up to set email alerts
|

A compendium of the histone H1 family of somatic subtypes: An elusive cast of characters and their characteristics

Abstract: The last 35 years has seen a substantial amount of information collected about the somatic H1 subtypes, yet much of this work has been overshadowed by research into highly divergent isoforms of H1, such as H5. Reports from several laboratories in the past few years have begun to call into question some of the traditional views regarding the general function of linker histones and their heterogeneity. Hence, the impression in some circles is that less is known about these ubiquitous nuclear proteins as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 0 publications
2
68
1
2
Order By: Relevance
“…The mouse has 6 somatic H1 variants (Parseghian & Hamkalo 2001) as well as testis-and oocyte-specific subtypes, and the systematic knockout of up to three somatic variants has provided animals and embryonic stem (ES) cells with a range of total H1 levels (Fan et al 2003(Fan et al , 2005. For each cell type, the content of each H1 subtype was quantitated by HPLC, and NRL values were determined from micrococcal nuclease digests.…”
Section: Nucleosome Repeat Length and H1mentioning
confidence: 99%
“…The mouse has 6 somatic H1 variants (Parseghian & Hamkalo 2001) as well as testis-and oocyte-specific subtypes, and the systematic knockout of up to three somatic variants has provided animals and embryonic stem (ES) cells with a range of total H1 levels (Fan et al 2003(Fan et al , 2005. For each cell type, the content of each H1 subtype was quantitated by HPLC, and NRL values were determined from micrococcal nuclease digests.…”
Section: Nucleosome Repeat Length and H1mentioning
confidence: 99%
“…4): [1] no immunoreactivity for the hH1FOO antibody and persistence of condensed chromatin (15 oocytes, 45%), [2] immunoreactivity for hH1FOO with persistence of condensed chromatin (3 oocytes, 9%), and [3] immunoreactivity for hH1FOO with decondensed chromatin (15 oocytes 45%). Interestingly, none of the oocytes contained sperm that showed decondensation but were nonreactive to the hH1foo antibody.…”
Section: Replacement Of Protamine By Hh1foo In Unfertilized Oocytes Amentioning
confidence: 99%
“…A previous cytogenetic study of unfertilized human oocytes after ICSI revealed various outcomes of the injected sperm: [1] the entire sperm was missing or was ejected outside the ooplasm, [2] sperm chromatin was undecondensed, or [3] there was variable premature chromosome condensation (27). Among these outcomes, failure of decondensation may arise from incomplete immobilization of sperm due to insufficient damage to the sperm plasma membrane.…”
Section: Early Incorporation Of H1foo Into Sperm Chromatin Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…H1 histones exist in multiple forms and have similar amino acid compositions but are hypothesized to have very distinct functions [2,3]. The sequences encoding these genes show a high degree of gene polymorphism; in mammals, these polymorphisms result in five to eight subtypes with distinct biological functions.…”
Section: Introductionmentioning
confidence: 99%